Еfficacy of Combined Treatment of Epithelial and Endothelial Corneal Dystrophy Using Corneal Crosslinking and Automated Posterior Lamellar Keratoplasty - L. R. Marvanova (Oftalʹmologiâ, 2019)
The purpose: to establish a combined approach to the treatment of patients with epithelial and endothelial cornea dystrophy (EED) based on a comparative study of the results of one-step and two-step methods. Patients and methods. The study included 75 patients (81 eyes) with corneal EED, who underwent surgical treatment at the Ufa Eye Research Institute from 2011 to 2016. The patients were divided into two groups — the main group consisted of 43 (46 eyes, 57 %) patients, who underwent the first stage of the CC before surgical treatment of EED, the second stage after 1–12 months — automated posterior lamellar keratoplasty (APLK). In the control group, isolated APLK was performed in 32 (35 eyes, 43 %) patients. Results. After CC (1–10 days) in the main group an increase in corneal thickness due to edema enhancement in the cornea stroma was observed in patients with stage I–III of the corneal EED. After 3 months, a decrease in corneal thickness was recorded in patients of the main group with I-II stages of the disease (p < 0.05), after 6 months — in all stages of the corneal EED compared with the control group (p < 0.05). According to optical coherence tomography (OCT), a decrease in the total cornea thickness in both зфешутеы groups was noted within 12 months after APLK: in the main group from 667 ± 65 μm initially to 594 ± 31 μm, in the control group, where there was a pronounced corneal edema from 787 ± 56 to 612 ± 67 μm. Conclusion. Corneal cross-linking in patients with I–III stages of corneal EED provides improvement of the cornea, manifested in reducing edema and its thickness. It allows to delay the implementation of the automated posterior lamellar keratoplasty without corneal deterioration in patients with stage I up to 6–12 months, in patients with stage II–III up to 3–6 months.